2007
DOI: 10.1177/1043659607305190
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Use of Home Care Services by Anglo-American and Mexican American Elders

Abstract: Elders' use of home care services varies globally. The authors tested the relationship of cultural/ethnic, contextual, and social structural factors with elders' use of home care services in the United States. Fifty-seven non-Hispanic White or "Anglo" and 56 Mexican American elders participated. Use of services significantly correlated with Anglo and Mexican American elders' cultural/ethnic and contextual factors. Perceived need and service awareness were the two factors that were significant for both groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 48 publications
(61 reference statements)
1
28
0
Order By: Relevance
“…Some evidence indicates that Mexican American caregivers report more distress than non-Hispanic White and African American caregivers (Adams, Aranda, Kemp, & Takagi, 2002; Aranda, Villa, Trejo, Ramírez, & Ranney, 2003; Folsom et al, 2007) and that Mexican American caregivers are more distressed than their noncaregiving counterparts (Hahn, Kim, & Chiriboga, 2011; Hernandez & Bigatti, 2010; Herrera et al, 2013). Yet, previous research on Mexican American caregivers tends to focus on small clinical samples, the elderly's use of formal care services, or care provided to children and spouses (e.g., Crist, Woo, & Choi, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Some evidence indicates that Mexican American caregivers report more distress than non-Hispanic White and African American caregivers (Adams, Aranda, Kemp, & Takagi, 2002; Aranda, Villa, Trejo, Ramírez, & Ranney, 2003; Folsom et al, 2007) and that Mexican American caregivers are more distressed than their noncaregiving counterparts (Hahn, Kim, & Chiriboga, 2011; Hernandez & Bigatti, 2010; Herrera et al, 2013). Yet, previous research on Mexican American caregivers tends to focus on small clinical samples, the elderly's use of formal care services, or care provided to children and spouses (e.g., Crist, Woo, & Choi, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Our findings build on qualitative studies that examine how changing cultural traditions in the Mexican-origin family relate to parental care (Crist, Garcia-Smith, & Phillips, 2006; Crist et al, 2007; A. P. Herrera et al, 2008; Mausbach et al, 2004; Radina, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Most research has focused on caregiver burden and psychological distress or the role of cultural factors like familism (Aranda & Knight 1999; Crist et al 2007; Hernandez & Bigatti 2010; Hahn et al 2011; Sayegh & Knight 2011). A recent study using this sample found that lower income Mexican-origin caregivers report more psychological distress than their higher income counterparts (blind citation).…”
Section: Mexican-origin Families Demographic Shifts and Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirby & Lau (2010) show that proportionally more African American and Hispanic older adults used any formal home care than Whites or Asian elders between 2000 and 2006. CMS data (as cited in Crist, Woo, & Choi, 2007) suggest that Mexican Americans use home health service less than White Americans (CMS, 2003). Yeboah-Korang, Kleppinger, and Fortinsky (2011) found that African American and Hispanic patients were less likely to receive physical therapy than White patients.…”
Section: Health Disparitymentioning
confidence: 96%